Stylistic Analysis of Male Commentators on Indonesian Pandemic In Channel News Asia - Muhammad Yurilsya (English Language Teaching Prima Journal (ELT), 2022)
Language style is the way people manipulate others and control their interaction in bringing messages or ideas conveyed in word and tone of voice. The characteristics of language style are: selecting and choosing the linguistic forms appeared from a person or group of people. In conducting this research, the researcher uses documentation method in collecting the data and applied qualitative descriptive analysis in analyzing the types of language style. The data of this research is the sentence and phrase of the comments used by male commentators. The data is analyzed based on the theory of Language style that proposed by Joos. The results of this research are, the male commentators employed the types of language style in giving comments to the video. Language styles used by male commentators are Consultative style, Casual style, and Intimate style. However, Frozen style and Formal style are not used. Therefore, male commentators only used 3 language styles and female commentators used four language styles. Those types of language style are realized with different realization. Those types of language style are realized in these comments because that is the standard in giving a comment and the male commentators applied the types of language style in order to give the comment by using complex sentence and well structured, to do a semiformal communication which words are chosen with care, to give a comment such among friends with the informal situation, and to give a comment by intimate family or friends. It could be concluded that types of language style are realized by the male commentators. Key Words: Stylistic Analysis, Language Style, Sentences, Male and Female Commentators, Channel News Asia